2006
DOI: 10.1080/10253890601029751
|View full text |Cite
|
Sign up to set email alerts
|

Examination stress as an ecological inducer of cortisol and psychological responses to stress in undergraduate students

Abstract: The purpose of the present study was to investigate basic methodological issues related to the usage of an examination stress protocol in studies of psychoneuroendocrinology. In the present study, 57 undergraduate students served as participants. All subjects provided salivary samples and completed psychological inventories during a low examination stress period and again during a high examination stress period. Salivary samples were analyzed for cortisol. Three major findings were observed. First, the examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 43 publications
12
44
0
Order By: Relevance
“…The lack of significant positive correlation between elevations in cortisol and elevations in psychological stress during the examination period was in agreement with the study by Weekes et al, 7 who reported no significant correlations in cortisol and elevations in psychological stress measures. However, the causal relationship between increase in stress hormone and serum lipid levels could not be established by the present study although they have same precursor skeletal structure.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The lack of significant positive correlation between elevations in cortisol and elevations in psychological stress during the examination period was in agreement with the study by Weekes et al, 7 who reported no significant correlations in cortisol and elevations in psychological stress measures. However, the causal relationship between increase in stress hormone and serum lipid levels could not be established by the present study although they have same precursor skeletal structure.…”
Section: Discussionsupporting
confidence: 82%
“…While a few studies have found significant positive correlations between psychological and hormonal measures of stress, others have found no significant correlations between these measures, or even negative correlations between these measures 6,7 . Since serum cortisol has similar primary structure (cyclopentanoperhydrophenanthrene ring system) as steroids and lipids, and lipids are usually metabolized to release energy, there may be a possibility of examination stress affecting the lipid profile in the body.…”
Section: African Health Sciences Vol 15 Issue 1 March 2015mentioning
confidence: 99%
“…There are also differences in stress responses by gender that we do not thoroughly explore in this paper (Del Giudice et al, 2011;Sauro et al, 2003;Stroud, Salovey, & Epel, 2002;Weekes et al, 2006). In particular, males may be more responsive to achievement-related stressors, whereas females may be more responsive to social rejection (Stroud et al, 2002).…”
Section: Gender Differences and Developmental Changes In Stress And Smentioning
confidence: 99%
“…In addition, based on a large body of literature showing that cortisol levels increase in response to naturalistic acute stressors (e.g., Weekes et al, 2006), we would expect to find that changes in cortisol would parallel the increase in IL-6 in this research. An important extension of this work will be to examine the simultaneous or differential trajectories of these physiological systems.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%